Types of Adolescent Fears - Siddiqov Sardorbek Zafarjon o’g’li (Journal of Higher Education and Academic Advancement, 2024)
Fear is a natural and useful companion throughout life. The study attempts to identify the fears of 15-year-olds. Fear of losing someone, fear of someone/something is the top category, followed by fear of death and worry about friends and family. Common fears come in second place, represented by fear of failure and fear of the future. The third largest category is the category of school-related fears. Differences in the emergence of fear are discussed depending on gender and developmental stage.